Data Services for Real Time Optimization of DC Nanogrids with Organic Growth. (December 2016) - Magnasco, Annika; Kirchhoff, Hannes; Chowdhury, Shahriar; Groh, Sebastian
Abstract: In the context of the rural electrification challenge, sharing-based nanogrids represent an innovative approach for affordable and sustainable electricity. The peer-to-peer topology of these nanogrids is targeted at organic growth and thus requires real time monitoring and optimization. A data analysis tool has been developed, aiming at achieving an efficient power flow and real time optimization of generation, storage, load and distribution capacities. This paper elaborates the core algorithms of the network topology optimization and provides first results based on data from a pilot nanogrid in Bangladesh.